The BLDC and Stepping Motor Control Firmware Programming to Improve Efficiency of SVF Extraction - Yeom, Hojun; ., . (International Journal of Engineering and Technology, 2018)
One of the most accessible and abundant amounts of adult stem cells is the isolation of adipose stem cells from adipose tissue. Centrifugation techniques are very important for obtaining these adipocytes. We used MCU to control high-speed BLDC motors and used stm32f407 of Cortex-M4 series which can perform high-performance and many processing. The motor was controlled by can communication for centrifugation, and PWM control of the stepping motor was performed to separate the extract. The optical sensor was also used to determine the type of extract. The optimal rpm of the improved product is expected to be 6,000. We confirmed the normal operation of the motor with the firmware program created through this study. The protocol optimized for SVF is implemented by controlling the rate of motor speed control and deceleration acceleration Â Â